Pengaruh Penerapan Metode Snowball Throwing Terhadap Hasil Belajar Pendidikan Agama Islam Di Kelas VII SMP Negeri 2 Sitiung Kabupaten Dharmasraya - Armadani Armadani; Darul Ilmi; Afrinaldi Afrinaldi; Fauzan Fauzan (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
Researchers found several weaknesses during PAI learning at SMP Negeri 2 Sitiung, namely the lack of enthusiasm of students to learn, low student achievement during learning, and there were still many students who fell asleep during learning, which affected learning. Learners influence learning. The aim of this research was to see how much influence the application of the snowball throwing method had on the Islamic religious education learning outcomes of class VII students at SMP Negeri 2 Sitiung, Dharmasraya Regency. This research is experimental research with a quasi-experimental design. The location for this experiment was carried out at SMP Negeri 2 Sitiung, Dharmasraya Regency. The population in this study was all students in class VII of SMP Negeri 2 Sitiung, a total of 57 students, while the sample in this study was class VII A, which was the experimental class, which had a total of 29 students, and class VII B, which was the control class, which had a total of 28 students. . In determining the sample in this research, aggregate sampling techniques were used. In this research, data was collected in the form of tests. Based on the results of data analysis, the snowball throwing method influences student learning outcomes by 71.4% and other factors by 28.6%. In the hypothesis test analysis, the significance value (two-tailed) was obtained, namely 0.026 < 0.05, so that the Ha test decision was accepted and Ho was rejected, so it can be concluded that the snowball throwing method has an effect on learning outcomes. Based on research data, it can be concluded that the snowball throwing method is more suitable for implementing teaching and learning in Islamic religious education.